IMPROVED HARDNESS AND CORROSION BEHAVIOUR OF ALUMINIUM 6061 ALLOY THROUGH ECAP PROCESSING - Sekaringgalih, Ratri; Putrayasa, I. Nyoman Gede; Puspasari, Vinda; Wardono, Joko Tri; Yustisia, Ari; Ari Kurniawan (Jurusan Teknik Mesin, Fakultas Teknik, Universitas Brawijaya, 2025)
The study was done to evaluate the effect of equal channel angular pressing (ECAP) processing on the hardness, optical morphology, and corrosion behavior of Al-6061 alloy. The samples were first annealed, and continued with ECAP process using the Bc route at 120° of internal channel angle with variation of passes (one, two, three, and four). The examination of corrosion resistance of Al-6061 alloy was examined using open circuit potential measurement, tafel polarization, and cyclic polarization. Moreover, the morphology of Al-6061’s surface after corrosion test was also studied using an optical microscope. The hardness test increased gradually with the addition of pass number in ECAP processing from 48.60 HB (0-pass) to 110.8 HB (4-passes). ECAP processing affects the microstructure of Al-6061 alloy, where the elongated grains are aligned parallel to the extrusion direction. Furthermore, the grain size of samples with higher pass numbers is more homogeny than samples with lower pass numbers. Meanwhile, the Tafel Polarization curves showed that ECAP processing in all samples decreased the corrosion rate from 0.6263 mmpy (as-annealed sample) to 0.1508 mmpy (4-passes sample). This phenomenon reveals that the corrosion resistance of Al-6061 alloy samples raises by the existence of ECAP processing. According to the morphological observation of Al-6061 samples, grain refinement due to ECAP processing could improve corrosion resistance.